Collision kinematics in the western external Alps. Issue 6 (11th June 2014) - Bellahsen, N.; Mouthereau, F.; Boutoux, A.; Bellanger, M.; Lacombe, O.; Jolivet, L.; Rolland, Y.
Abstract The kinematics of the collision in Western Alps are investigated through five balanced cross sections of the whole external domain from the Oisans to the Mont Blanc massif. These cross sections were built using published data for the Jura and subalpine fold‐and‐thrust belts and new structural and field analysis for the External Crystalline Massifs. Five units are defined: the sedimentary nappes from innermost parts of the external zone (e.g., ultra‐Dauphinois/Helvetic), the crystalline units with their dysharmonically folded cover (e.g., Morcles nappe), sedimentary nappes over the frontal parts of the crystalline massifs (the Aravis‐Granier unit), the subalpine belts (e.g., Vercors, Chartreuse, Bauges, and Bornes), and the Jura. Except for the ultra‐Dauphinois nappes, the shortening, including the cover shortening, always corresponds to basement shortening. The total amount of shortening increases from south (28 km, 20%) to north (66 km, 27%). Moreover, the shortening is slightly older in the south than in the north; deepwater turbidites (flysch) and shallow marine to freshwater clastics (molasse) basins are more developed in the north; pressure and temperature conditions are higher in the north; the average uplift rates are about 3 times higher in the north and more localized in space. We propose that these differences are due to along‐strike variations in the structure of the European continental margin inherited from Mesozoic times. We then build five palinspastic maps: one at Cretaceous times showing the inherited European Mesozoic margin structure and four from Priabonian to upper Miocene times showing the collision kinematics and the related rotation of Adria.